The Society Perception Toward Harmonization of Social Relationship Ethnic in Malaysia - Nurjanah, Igus; Mat Arifin, Anis Satila Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research to describe society perceptions of the harmonization of ethnic social relations in Malaysia. Malaysia is a multi-ethnic, multi-cultural and multi-lingual society. This type of research is qualitative descriptive, using several informants to conduct interviews. Data sources used are primary sources, namely information that is sourced directly from the research location by means of interviews. Whereas secondary sources are data obtained from documentation or literature study to complete primary data, with sampling technique, accidental sampling. The results of the research show that social relations between ethnic groups in Malaysia have been well established by maintaining togetherness and mutual respect between individuals and community groups. However, both the community and the government still have to strive to keep working together in maintaining the harmony of social relations that have been well established, so that the creation of a sense of security and comfort despite being in an environment with ethnic diversity.